对比《长日留痕》和《长日将尽》与中国、台湾文化和翻译策略差异之关系 = Comparing the China and Taiwan translations of the remains of the Day using cultural differences and translation strategies as basis of comparison - 陈欣怡 Tan, Samantha Xinyi (2019)
石黑一雄 (Kazuo Ishiguro) 是一位著名日裔英国作家。他在1954年出身于日本长崎，5岁时随家搬到英国。他在英国肯特大学学习英语和哲学，后来到东安格利亚大学学习创作。他的代表作包括《长日留痕》（又译《长日将尽》）和《别让我走》，《长日留痕》（又译《长日将尽》）在1989年获得英语文学重要奖项布克奖。2017年，石黑一雄获得了诺贝尔文学奖。至今，石黑一雄的作品已被翻译成超过三十种语言。虽然 1994 年由台北皇冠出版社推出的余而彦所译的《长日将尽》译本和 2008 年由南京译林出版社推出的冒国安所译的《长日留痕》译本都是在进行语际翻译，从英语（原语）翻译成华语（译语），但是两本译本之间存在着差异。由于种种原因，中国和台湾存在着三十多年完全隔绝的状态，在经济、文化上的完全隔绝，导致翻译时出现差异。本文会以译者采用的各别翻译策略、中国与台湾在文化习俗上的差异以及译本与原文出现的误译，分析之间的差异。Kazuo Ishiguro is a Japanese-born British novelist. He was born in Nagasaki, Japan in 1954 and emigrated to Britain with his family at the age of 5. He studied English Literature and Philosophy at the University of Kent and then creative writing at the University of East Anglia. Ishiguro’s representative works include The Remains of the Day and Never Let Me Go. The novel The Remains of the Day won the Man Booker Prize in 1989. In 2017, Kazuo Ishiguro won the Nobel Prize in Literature. Till date, Ishiguro’s works have been translated into more than 30 languages worldwide. The Taiwan translation and the China translation of the original novel differs in some aspects despite both translations being interlingual translations, translating from English (Source Language) to Chinese (Target Language). Due to various differences, China and Taiwan were in complete isolation for more than thirty years, without any interactions in culture and economy, leading to differences in the translations. Using the various translations strategies employed by the translators, differences in culture and traditions between China and Taiwan as well as the presence of mistranslations between the Source Text (ST) and the Translated Texts (TT) as basis of comparison, this paper will analyze the differences between the China TT and the Taiwan TT.